Fully-automated estimation of upper cervical cord cross-sectional area using pontomedullary junction referencing in multiple sclerosis - Masciullo, Roberto; Sutter, Annine; Sacco, Rosaria; Pinna, Nicola; Distefano, Daniela; Pravatà, Emanuele; Mallucci, Giulia; Cianfoni, Alessandro; Gobbi, Claudio; Zecca, Chiara; Disanto, Giulio (Frontiers in Neuroimaging, 2025)
BackgroundSpinal cord cross-sectional area (CSA) is a biomarker of disability in multiple sclerosis (MS). Vertebral-based CSA suffers from anatomical variability and positional bias.ObjectivesTo evaluate a fully automated PMJ-referenced approach, as implemented in the open-source Spinal Cord Toolbox, to assess cervical cord CSA at a fixed distance from the pontomedullary junction (PMJ) in MS.MethodsRetrospective study performed at the MS center of Lugano (Switzerland). Inclusion criteria were treatment with natalizumab or ocrelizumab and absence of clinical/radiological disease activity over ≥2 years. CSA at 64 mm caudal to the PMJ (CSA PMJ) and at C2–C3 vertebral level (CSA C2–C3) were calculated using the Spinal Cord Toolbox.ResultsSeventy-five MS patients [females = 44 (58.7%), age = 45.1 (36.7–53.8) years, natalizumab = 36 (48%), ocrelizumab = 39 (52%)] were included. Median CSA PMJ and CSA C2–C3 were 57.7 (53.1–62.1) and 58.1 (53.2–62.6) mm2, respectively. The two measures were highly correlated (rho = 0.95, p < 0.001), with some exceptions related to errors in vertebral labelling in CSA C2–C3 assessments. PMJ was correctly identified in all subjects. CSA PMJ measures were negatively associated with disability (β = −0.08, p = 0.002), independent of age and sex.ConclusionAutomated measurement of spinal cord CSA at fixed distance from the PMJ is applicable in MS, performs better than vertebral-based CSA, and correlates with neurological disability.